Synergistic effects of Bacillus salmalaya strain 139SI with fertilizer on nutrient uptake and fertilizer use efficiency of oil palm seedlings - Ponari, Md Hoirul Azri; Ismail, Salmah; Abdullah, Rosazlin (Malaysian Society for Microbiology, 2024)
Aims: Plant-microbe interaction in the rhizosphere significantly influences nutrient uptake efficiency. Thus, this research was aimed to investigate the potential of Bacillus salmalaya strain 139SI in increasing nutrient use efficiency through its synergistic effects with fertilizer application.